Coral assemblages and environments from Bajocian reefs in the Western Carpathians - Lathuilière, Bernard; Schlögl, Ján; Tomašových, Adam; Ivanova, Daria K. (Geobios, 2023)
The systematics of the coral assemblages of the Vršatec Limestone from the Pieniny Klippen Belt (Western Carpathians) that inhabited the NW Tethyan margin during the Bajocian is revisited here based on a new and extensive sampling of coral specimens collected at four outcrops. The assemblage consists of 12 genera and 13 species, including the new species Proaplophyllia slovakensis and the first Bajocian occurrence of the genus Enallhelia. Morphometric analyses also allow us to synonymize multiple species citations of the genus Thecosmilia into a single species. A quantitative study shows that five genera tend to be most common at all outcrops, namely Cladophyllia, Dendraraea, Isastrea, Periseris, and Thecosmilia, documenting relatively high homogeneity in the qualitative generic composition of coral assemblages but quantitative differences among the four outcrops. Coral specimens are frequently affected by macroborings (Gastrochaenolites, Entobia, and Trypanites) and coated by microbialitic components. We suggest that these reefs grew in the optimum of the Bajocian reefal window (i.e., shallow-water photic environments above storm wave base). We also identify three traps (typological, nominal, and induction traps) that led in the past to the false stratigraphic attribution of these reefs, when they were erroneously assigned to the Oxfordian rather than to the Bajocian.